Calcium disodium ethylenediaminetetraacetate as a safe compound for crop protection with the potential to extend the basic substances group - Martin Žabka; Roman Pavela; Martina Trávníčková; Martin Barnet (Plant Protection Science, 2020)
Excessive use of commercial synthetic fungicides in agriculture is a globally discussed issue. This topic is seen as particularly important in modern plant protection and cultivation systems, where the total fungicide burden of the agroecosystem should be controlled and reduced. Basic substances (BSs) are a relatively novel, legally recognised group of substances which can be applied. The present study tested calcium disodium ethylenediaminetetraacetate (CaNa2-EDTA), a substance whose properties and environmental safety make it another useful alternative for plant protection in modern farming. The study demonstrated the high antifungal activity of the substance against Pyrenophora (anamorph: Drechslera) tritici-repentis (Died.) Drechsler, (MIC50 0.195-0.223 mg/ml), safety for plant tissue and especially for non-target organisms, and positive effects on the yield of wheat (Triticum aestivum Linnaeus). CaNa2-EDTA surpassed the effect of chitosan hydrochloride, a registered and utilised substance, and a synthetic conventional fungicide. CaNa2-EDTA is an excellent candidate for registering within the BS group, with benefits for environmentally sound systems in plant protection.